2022
DOI: 10.1001/jamasurg.2021.7567
|View full text |Cite
|
Sign up to set email alerts
|

Association Between High-Deductible Health Plans and Hernia Acuity

Abstract: IMPORTANCE About half of people younger than 65 years with private insurance are enrolled in a high-deductible health plan (HDHP). While these plans entail substantially higher out-of-pocket costs for patients with chronic medical conditions who require ongoing care, their effect on patients undergoing surgery who require acute care is poorly understood. It is plausible that higher out-of-pocket costs may lead to delays in care and more complex surgical conditions. OBJECTIVE To determine the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…[2][3][4] High out-ofpocket costs represent a substantial financial burden for some patients, who may then forgo or delay necessary care. 5,6 To improve patient care and combat rising prices, the Centers for Medicare & Medicaid Services (CMS) passed the Hospital Price Transparency Final Rule, which requires that hospitals publish their standard charges in a publicly available, machine-readable file. 7 Price transparency is a prerequisite for price shopping, and according to standard economic theory, price shopping ensures that identical goods at different locations have the same price (the Law of One Price).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] High out-ofpocket costs represent a substantial financial burden for some patients, who may then forgo or delay necessary care. 5,6 To improve patient care and combat rising prices, the Centers for Medicare & Medicaid Services (CMS) passed the Hospital Price Transparency Final Rule, which requires that hospitals publish their standard charges in a publicly available, machine-readable file. 7 Price transparency is a prerequisite for price shopping, and according to standard economic theory, price shopping ensures that identical goods at different locations have the same price (the Law of One Price).…”
Section: Introductionmentioning
confidence: 99%
“…For the 31.6 million US individuals without health insurance and the 40% of privately insured US individuals with high-deductible health plans, these high prices can translate to high out-of-pocket costs . High out-of-pocket costs represent a substantial financial burden for some patients, who may then forgo or delay necessary care …”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29] However, our findings add to more recent evidence that should increase caution about potential unintended and negative consequences of HDHPs. For instance, Yelorda et al 30 found that hernia patients enrolled in HDHPs were more like to have findings of incarceration or strangulation, and an analysis by Loehrer et al 31 identified an association between higher degrees of cost-sharing and early uncomplicated presentation for acute appendicitis and acute diverticulitis. However, neither of these studies had the ability to comment on rates of catastrophic health spending or on variations across race, ethnicity, or income.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has shown that increased cost-sharing is associated with decreased utilization of health services, including both indicated or beneficiary services and more discretionary or unneeded services 4–6 . The present study builds on growing evidence that increasing patient cost-sharing, here specifically through high-deductible plans, is associated with delays in presentation, more severe disease, and ultimately much higher rates of CHEs for patients with common surgical conditions 7,8 . In addition, Scott and colleagues were able to evaluate variation by patient race/ethnicity and income.…”
mentioning
confidence: 89%
“…much higher rates of CHEs for patients with common surgical conditions. 7,8 In addition, Scott and colleagues were able to evaluate variation by patient race/ethnicity and income. Perhaps not surprisingly, these findings only further underscore the broader socioeconomic and racial inequity in the United States, especially via the wealth gap.…”
mentioning
confidence: 99%